A novel steam ejector with auxiliary entrainment for energy conservation and performance optimization. (15th September 2017) - Tang, Yongzhi; Li, Yanxia; Liu, Zhongliang; Wu, Hongqiang; Fu, Weina
Highlights: There exist several low-pressure regions inside the steam ejector. A novel steam ejector with auxiliary entrainment is proposed. This novel ejector can suck extra entrained steam for performance improvement. There is an optimum auxiliary entrainment scheme under given operation conditions. Abstract: In this study, it is found that there exist several low-pressure regions whose pressure is lower than that of the entrained steam inside the ejector under both its designed and non-designed conditions. Thus a novel steam ejector with auxiliary entrainment is proposed to take full use of the possible low-pressure regions to entrain the extra low-grade entrained steam for energy conservation and performance improvement. The internal flow fields in the steam ejector with and without auxiliary entrainment have been obtained numerically. Analysis and research are mainly focused on the influences of the mixing chamber, ejector throat, diffuser auxiliary and combined auxiliary entrainment on the mass flow rate, the entrainment ratio, the internal pressure field and the shock wave phenomena of a given ejector. The results reveal that the throat and diffuser auxiliary entrainment can increase the entrainment ratio of the steam ejector under the simulated operation conditions. The throat auxiliary entrainment is a feasible choice for ejectors operating under the designed conditions and the combined auxiliary entrainment of the throat and the diffuser is the best choice for ejectors operating under non-designed conditions.